Zn-, Cu- or Ag-incorporated micro-arc coatings on titanium alloys: Properties and behavior in synthetic biological media; Surface and Coatings Technology; Vol. 369 - Sedelnikova M. B. Mariya Borisovna; Komarova E. G. Ekaterina Gennadjevna; Sharkeev Yu. P. Yury Petrovich; Ugodchikova A. V. Anna Vladimirovna; Mushtovatova L. S. Lyudmila; Karpova M. R. Mariya Rostislavovna; Sheikin V. V. Vladimir; Litvinova L. S.; Khlusov I. A. Igor Albertovich (2019, 2019)
Title screen